2023
DOI: 10.3233/wor-220230
|View full text |Cite
|
Sign up to set email alerts
|

Examining psychosocial factors associated with receiving workplace accommodations among people with disabilities

Abstract: BACKGROUND: People with disabilities experience challenges in obtaining workplace support including job accommodations. OBJECTIVE: This study examined the impacts of psychosocial factors affecting the likelihood of an employee with disability receiving an accommodation and subsequent effects on job satisfaction and job performance. METHODS: This study recruited 596 participants from multiple national and state agencies serving persons with disabilities in U.S. A mediation model was conducted to examine the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
0
0
1
Order By: Relevance
“…The findings indicate that competence in individually evaluating the impact of various cognitive impairments and how these can be reduced by self-management strategies and adjustments in work is needed. This is in line with research highlighting the need of including professionals with expertise in rehabilitation to facilitate a supportive work environment [45,46].…”
Section: Discussionsupporting
confidence: 84%
“…The findings indicate that competence in individually evaluating the impact of various cognitive impairments and how these can be reduced by self-management strategies and adjustments in work is needed. This is in line with research highlighting the need of including professionals with expertise in rehabilitation to facilitate a supportive work environment [45,46].…”
Section: Discussionsupporting
confidence: 84%
“…11 La discapacidad total estuvo relacionada principalmente a la calidad de vida dominio físico de salud con el Rho de -0,510 con Pvalor de 0, se determina que la discapacidad afecta la calidad de vida física, estaría supeditada a la posibilidad y capacidad de realizar actividades con la independencia y facilidad anterior al evento, considerando que existe una escasa superación para las actividades diarias y de trabajo, relacionado a un funcionamiento menor en relación a personas sin limitaciones, lo que incluso puede inferir en la posibilidad de conseguir trabajo o desempeñar funciones de manera adecuada. 12 La calidad de vida general se la percibió con relación moderada en primer lugar al dominio de cuidado personal de la discapacidad con un Rho -0,478 y Pvalor de 0; lo que guarda relación por cuanto existiría una dificultad en realizar las actividades diarias de cuidado personal por tener una característica de predominio físico y relacionado a mayor frecuencia de lesiones de miembro superior como se comentó anteriormente. 13 Mientras que dentro del dominio específico de calidad de vida en cuanto a la salud física tuvo mayor relación con la discapacidad de actividades remuneradas con resultado de Rho de -0,473 y P valor de 0; siendo algo esperado ya que la población mayormente afectada fueron trabajadores operativos o de actividades de predominio manual; y con la subsiguiente consideración de presencia de lesiones por amputaciones de dedos de mano; siendo un grupo encuestado netamente laboral, sienten que su calidad de vida física se ve afectada con una mayor percepción de discapacidad para afrontar sus tareas laborales.…”
Section: Resultsunclassified
“…Although the study by Jazayeri et al 1 is restricted to one of the rheumatic diseases and to Canadian patients only, numerous studies have addressed the issues of job accommodation in other rheumatic diseases and other causes of disabilities. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] It is interesting that in systemic lupus erythematosus, the most common job accommodation used was sick leave days, which is not an unusual accommodation and does not require any true workplace adaptations. 4 It has been found that inclusive and supportive workplace environments-not employee psychosocial factors-are the key factors in increasing the likelihood of receiving accommodations as well as the subsequent association between receiving the accommodation and job satisfaction.…”
mentioning
confidence: 99%
“…4 It has been found that inclusive and supportive workplace environments-not employee psychosocial factors-are the key factors in increasing the likelihood of receiving accommodations as well as the subsequent association between receiving the accommodation and job satisfaction. 5 However, it is also true that many patients with arthritis do not use their benefits and/or accommodations until needed, and in those who use them, the various employment outcomes were generally positive. 7 Episodic or intermittent disability is also an important issue and perhaps needs to be addressed differently from permanent disabilities.…”
mentioning
confidence: 99%